An Interactive Voice Response Diary for Patients with Nondystrophic Myotonia - Statland, Jeffrey M (2011)
INTRODUCTION: Nondystrophic myotonia (NDM) is caused by mutations in muscle chloride and sodium channels. Currently there is no standardized instrument for documenting symptom frequency and severity in NDM. METHODS: Subjects used an automated interactive telephone-based voice response diary (IVR) to record frequency and severity of stiffness, weakness, pain, and tiredness once a week for 8 weeks following their baseline visits. RESULTS: Here we describe the IVR and report data on 76 subjects for a total of 385 person-weeks. Overall there were 5.1 calls per subject. Forty-eight subjects called in 5 or more times, and 14 called in 8 times. Stiffness was both the most frequent and severe symptom. Warm-up and handgrip myotonia were associated with higher severity scores for stiffness. DISCUSSION: IVR is a convenient technology to allow patient reporting of repeated and real-time symptom frequency and severity, and is being used in a trial of mexiletine in NDM.